KETERKAITAN FAKTOR JARINGAN ADIPOSA DAN OBESITAS YANG MENDASARI TERJADINYA SINDROMA METABOLIK - Rita Kusuma; Surjadi Rimbun (Jurnal Kedokteran Methodist, 2025)
ABSTRACT With the increasing prevalence of physical inactivity, particularly in urban areas, and the widespread consumption of unhealthy foods, the prevalence of overweight and obesity (adiposity) has increased. This condition gives rise to a pathophysiological disorder in adipose tissue, an endocrine organ, known as metabolic syndrome. Atherogenic dyslipidemia significantly contributes to the development of atherosclerosis, which leads to cardiovascular disease. Inflammatory substances released by diseased fat cells also contribute to certain cancers. This review examines obesity and adipose tissue, which are fundamental to the development of metabolic syndrome, to deepen our understanding of metabolic syndrome and encourage further research to develop effective strategies for preventing and managing this complex metabolic disease. Keywords : Adipose tissue, OBESITY, METABOLIC SYNDROME